2020
DOI: 10.1109/tse.2018.2874470
|View full text |Cite
|
Sign up to set email alerts
|

How Do Users Revise Answers on Technical Q&A Websites? A Case Study on Stack Overflow

Abstract: To ensure the quality of its shared knowledge, Stack Overflow encourages users to revise answers through a badge system, which is based on quantitative measures (e.g., a badge is awarded after revising more than 500 answers). Prior studies show that badges can positively steer the user behavior on Stack Overflow (e.g., increasing user participation). However, little is known whether revision-related badges have a negative impact on the quality of revisions since some studies show that certain users may game in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Such findings are consistent with studies of the dynamics of Stack Overflow and other Q&A websites, where influence gaming is a real phenomenon [27], and experiments have shown effective ways to promote post or answer visibility and manipulate poster engagement [28]. Moreover, Wang et al [29] studied answer revision on Stack Overflow, finding that gamification stimulated posters to revise answers, although very active posters mostly made minor textual revisions, likely related to the high likelihood of revisions being reverted if a poster is very active.…”
Section: How Is Stack Overflow Used?supporting
confidence: 87%
See 1 more Smart Citation
“…Such findings are consistent with studies of the dynamics of Stack Overflow and other Q&A websites, where influence gaming is a real phenomenon [27], and experiments have shown effective ways to promote post or answer visibility and manipulate poster engagement [28]. Moreover, Wang et al [29] studied answer revision on Stack Overflow, finding that gamification stimulated posters to revise answers, although very active posters mostly made minor textual revisions, likely related to the high likelihood of revisions being reverted if a poster is very active.…”
Section: How Is Stack Overflow Used?supporting
confidence: 87%
“…(P4. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] We found affinity bias to explain this decision making, as some participants showed clear preference for solutions provided by others perceived to be like them, sharing some kind of shared identity (e.g., 'programmers'). Participants contextualized their rationale for wanting brief solutions with little explanation by their status "as coders", thereby preferring answers conforming to what they would expect from others in their social group.…”
Section: It Lets Me Just Copy and Pastementioning
confidence: 99%
“…Answerers are encouraged to include relevant information about the valid version or the time of their knowledge 31. https://en.wikipedia.org/wiki/Template:Dead link 32. https://stackoverflow.com/posts/comments/61093395/ when creating answers.…”
Section: Actionable Suggestions For Usersmentioning
confidence: 99%
“…The majority of prior studies define the quality of content on Stack Overflow from the presentation aspect (e.g., code and text) [ [30]. Wang et al analyzed how the badge system impacts answer revision on Stack Overflow, and found that the current system fails to consider the quality of revisions [31].…”
Section: Understanding and Improving The Quality Of Posts On Stack Ovmentioning
confidence: 99%
“…( Ortega et al, 2014 , Neshati, 2017 )). To ensure that competent answering is rewarded, SO is employing gamification mechanisms, distributing “badges” to esteemed responders and encouraging revisions and edits to posted questions and answers as well as the rapid answering of posts ( Papoutsoglou et al, 2020 , Wang et al, 2018a ).…”
Section: Related Workmentioning
confidence: 99%